Integrating Zero Trust Architecture with Service Mesh for Enhanced Cloud Security in DevOps Workflows - Dindigala, Raju; Dandyala, Sai Surya Mounika (Institut Teknologi Bisnis AAS Indonesia, 2024)
The increasing adoption of cloud-native architectures and DevOps workflows has revolutionized software development and deployment but has also introduced complex security challenges. To address these challenges, Zero Trust Architecture (ZTA) has emerged as a critical paradigm, emphasizing the principle of